Types of Uropathogens and Pattern of Antimicrobial Resistance among Urinary Tract Infected Patients Presenting to Primary Care: Uropathogens and Antimicrobial Resistance in Urinary Tract Patients - Badshah, Salim; Ullah, Farman; Rehman, Hammad Ur; Rehman, Abdur; Ghafoor, Adnan; Rind, Aslam (Pakistan Journal of Health Sciences, 2024)
Urinary Tract Infections (UTIs) were prevalent bacterial infections with significant public health impacts, particularly affecting females due to anatomical predispositions. Objective: To assess the types of uropathogens and their antimicrobial resistance profiles among patients with UTIs presenting to a private clinic in districts Dir Lower and Upper, Pakistan. Methods: A prospective observational study was conducted, enrolling 109 patients with symptoms suggestive of UTIs. Urine samples were collected and subjected to culture and sensitivity testing. Data on patient demographics, uropathogen identification, and antibiotic susceptibility patterns were analyzed using SPSS version 21.0. Results: Escherichia coli was the predominant uropathogen, isolated in 51.90% of patients, followed by Pseudomonas aeruginosa (12.00%), Enterococcus (9.80%), Staphylococcus aureus (3.80%), and Serratia odorifera (1.50%). Among Escherichia coli isolates, Nitrofurantoin exhibited the highest sensitivity (91.30%), while Ampicillin, Cefixime, Amoxicillin, and Ceftriaxone showed substantial resistance rates (>85%). Pseudomonas aeruginosa demonstrated high resistance to all tested antibiotics. Enterococcus and Staphylococcus aureus exhibited variable sensitivity patterns, while Serratia odorifera displayed uniform sensitivity to the antibiotics tested. Conclusions: Escherichia coli was the predominant uropathogen isolated among patients with UTIs in districts Dir Lower and Upper, Pakistan, with varying susceptibility patterns to commonly prescribed antibiotics.